Türk Hukukunun Avrupa Birliği Hukukuna Uyumu Özel Hukuk / Approximation of Turkish Law With European Union Law Private Law - Acquis Communautaire'in Alınması - Açıklamalar, Değerlendirmeler, Öneriler / - Transposition of Acquis Communautaire - Remarks, Assesments, Suggestions - Kaya, Arslan; Engin, Baki İlkay; Pasli, Ali; Asikoglu, Sehriban Ipek; Oguz, Elif (Istanbul University Press, 2020)
Approximation of Turkish Law with European Union Law maintains its importance and actuality apart from the context of full membership goal as well. Global trade requires interplay between all world countries with regard to the development and formation of public and private law. Private law regulations in Continental Europe, that constitute models for Turkish law, have been developing under the influence of European Union Law. In any field of law, the authority of the European Union to intervene in national laws is limited to the competences provided by the Treaties. Therefore, acts of the European Union in the field of private law aims the improvement of the internal market and enhanced cooperation between the Member States both by harmonization of national laws and their implementation. Studies and proposals carried out by the European Union for the harmonization of laws should be/are closely followed by our country. Establishment of Customs Union between Turkey and European Union in 1995 with the 1/95 numbered Community Council Decision and initiation of accession negotiations in October 2005 have accelerated the harmonization process of Turkish law with the European Union law. In the heat of these events, it can be observed that the preamble of most of the main codifications and secondary regulations in the field of company law, banking and capital markets law, intellectual and commercial property law, competition law, consumer law and protection of personal data law; reflects the aim of approximation with European Union legislation. Turkey's geographical location, parallelly the fact that majority of the states, which Turkey has economical, cultural and sociological relations with, are members of the European Union following the impact of European Union on the model laws of Turkish laws, including Swiss law which keep tab on European Union law, necessitates the harmonization of European Union law to remain on Turkish lawyers' agenda in the future as well. Hence, this Book Project has been prepared by the first documentation center acknowledged by European Union's competent publishing and distribution bodies, Istanbul University Faculty of Law European Law Application and Research Center, with the object of providing a source for publications and conferences of Turkish lawyers who are keen to work in this field. This Project is an academic study and reflects the evaluation of the authors on harmonization of Turkish law with European Union law and their opinions for the methodology for an approximation of Turkish legislation. Although it is not either an official report or an action plan, it has been prepared with the view of providing a reference to public authorities, especially Ministry of Foreign Affairs Directorate for European Union Affairs and European Union harmonization offices in other relevant ministries. The preparation phase of this Project includes determination of the subdisciplines of Turkish private law, in which harmonization with European Union law, has been taken in regard. The specification of a certain topic is left to the authors. As a matter of course, it was not possible for us to cover all the subdisciplines of private law likewise to examine the entire European Union acquis in the included fields. Our perspective is to provide an insight into European law, its comparison with European Union law and evaluation of alignment. With this regard, every contributor examined the regulation which includes the most general rules on that topic. Although the examined regulations have been enacted on the legal basis of the Treaties, the relevant articles have been explained under the "Remarks" title. In this way, with the exception of topics under "Competition Law" chapter, only the masthead of the acts of European Union organs are shown under the "Legislation" title. Besides, all the examined European Union legislation and their legal basis are shown in the European Union legislation list and index at the end of this book. Subdisciplines of private law to be studied has been designated taking into account several factors, such as the necessity of reevaluation and updating with the current acquis, despite the fact that Turkey's remarkable progress in the past according to the European Commission country reports; Ministry of European Union's Action Plan covering the years of 2016-2019; 11th development plan of Turkish Presidency. Thus, the Project touches on Company Law, Financial Services, Consumer and Health Protection, Intellectual Property chapters which have been opened for negotiations, and Competition Policy chapter that has not yet been opened for negotiation alongside the Protection Of Personal Data which is not itself a negotiation chapter but concerns several chapters of negotiation. Regulations in the aforementioned fields have been analyzed under the Company Law, Banking and Capital Markets Law, Intellectual and Commercial Property Law, Competition Law, Consumer Law and Protection of Personal Data Law main titles. Within the scope of the Project, contributors were expected to prepare their work according to the following outline: I. Legislation A. European Union Legislation B. Turkish Legislation; II. Remarks A. European Union Law, B. Turkish Law; III. Assessments and Suggestions. By this means, the necessity of the readers to get conveniently informed solely on the European Union Law or Turkish law related to that subject is considered. Assessments and suggestions have been provided under a separate title with the view of improving on the perception of approximation with European Union which only focuses on the translation of legislation and relation of European Union law with Turkish law can be put forward in an integrated mindset. Under this title, the conclusions reached by evaluating Turkish law and European Union law have been placed in numerical order. In other respects, contributors were provided flexibility in terms of methodology to be used for their remarks and assessments and freedom to include the Turkish translation of the relevant European Union legislation and place article proposals for Turkish legislation. Editorial Board elaborated on determining the main subjects and, alongside the review of all studies with respect to the fundamental aim of this book, providing for systematical coherence thereof.